Identification of high-value bioactive constituents in Northern European willow varieties: S.X. Dasyclados, Endeavour, Cheviot, Tora, Resolution, S. Purpurea, Terranova, endurance - Ayman Hijazi; Italo Pisano'; J.J. Leahy; Witold Kwapinski; Christopher R. Johnston; John Prendergast (Elsevier, 2022)
Willow trees have maintained their place in medicine for many years as they are herbal source of various cures. Willow varieties are considered to contain a wide range of anti-inflammatory and anti-bacterial species such as salicylates and flavonoids. The current work is centred on the presence of high bioactive pharmaceutical constituents other than salicin such as flavan-3-ol catechin, salicortin, and other complex compounds, which contribute to the total medical value of willow extracts. To evaluate the distribution of these bioactives, bark, and wood fractions of 8 different willow varieties (S.X. Dasyclados, Endeavour, Cheviot, Tora, Resolution, S. Purpurea, Terranova, Endurance) were extracted using dispersive solid phase extraction and then analysed using LC-MS comprising a quadrupole time-of-flight spectrometer. Indeed, various high value constituents such as salicortin, catechin, triandrin, acacetin-5-O-xyloside, picein, apigenin-7-O-glucoside, vitexin-2-rhamnoside, luteolin-7-glucoside, catechin gallate, and kaempferol as well as giberellic and 5-methoxysalicylic acid were detected in bark and wood fractions of the willow varieties 80:20 ethanol/water extracts.